Kriteria Kepemimpinan Pendidikan Islam Menurut Al-Ghazali - Najamul Wathan (Islam Universalia: International Journal of Islamic Studies and Social Sciences, 2019)
This research is a study of the thought of Al-Ghazali about Islamic education leadership criteria. The purpose of this study was to analyze the concept of Islamic education leadership criteria. This research applied library research. The results of this study are Al-Ghazali argued that the appointment of a leader is a syar'i obligation, not an aqli obligation. He emphasized the essence of Islam that Islam is a shari'a in the world and the hereafter. In addition, Al-Ghazali also argued that power was sacred because the people were obliged to follow all his orders. Power, according to Al-Ghazali, is mastering the hearts of the people. So that they can obey and respect all the rules that have been set. DOI: https://doi.org/10.5281/zenodo.3236460